Application of Deep Learning in Photovoltaic Array Fault Identification. Issue 4 (April 2021) - Han, Yuchen; Yao, Xiaodong
Abstract: If a photovoltaic power station needs to operate normally, it cannot do without the blessing of the photovoltaic array, which also takes up about half of the cost of the photovoltaic system. The failure and low efficiency of photovoltaic power plants are the main two reasons for the loss of energy. Among them, the failure of photovoltaic arrays is undoubtedly one of the important reasons. In this article, the author uses the superiority of deep neural network in fault identification technology to complete the fault identification model of photovoltaic array.